Business mathematics - Veena, G.R (Galgotia Publications Pvt. Ltd., 2004)
Using a text/workbook format to develop problem-solving skills, this book is designed to show how maths is used in real-world business situations. It includes a built-in study guide, "Quick Review", which provides a bird's eye overview of each chapter to help reinforce basic understanding and study skills.